Hyperinflammation readily resolved by dexamethasone in pediatric patients with hematological malignancies - Ćazić, Marija; Krstovski, Nada; Lazić, Jelena; Rodić, Predrag; Milošević, Goran; Škorić, Dejan; Janković, Srdja (Vojnosanitetski pregled, 2025)
Background/Aim. Hyperinflammatory syndromes are a relatively rare phenomenon, but can be life-threatening for children suffering from malignancy. Hemophagocytic lymphohistiocytosis (HLH) is perhaps the best recognized of several such hyperinflammatory syndromes that share a key aspect of pathogenesis – the “cytokine storm”. However, conditions that resemble HLH but do not fully meet its diagnostic criteria are not uncommon and often present a diagnostic challenge. The aim of this study was to examine clinical features, disease course, and response to dexamethasone treatment in children with hematological malignancy and hyperinflammation. Methods. This retrospective observational study analyzed medical records of 11 children (four females and seven males; median age 10.8 years, range 3.1–16.3 years) investigated for potential hyperinflammation during treatment for a hematological malignancy at the University Children’s Hospital in Belgrade, Serbia, from January 2023 to July 2024. Relevant clinical and laboratory parameters were retrieved (serum triglyceride concentration was measured in ten children), as well as data on potential triggers, dexamethasone treatment, and treatment outcome. Results. All children were febrile. Bicytopenia/pancytopenia was noted in six (54.5%), and splenomegaly in two (18.2%) children. Bone marrow aspiration was performed in nine children, and no hemophagocytosis was observed. Serum triglyceride concentration was elevated in one (10.0%) child. Fibrinogen levels were above 1.5 g/L in all cases, and ferritin levels exceeded 500 μg/L in ten (90.1%) children. Two (18.2%) children had soluble interleukin-2 receptor (sIL-2R) above 2,400 IU/mL (the median sIL-2R level was 1,041 IU/mL, range 396–9,069 IU/mL, and the interquartile range was 1,012 IU/mL). Only one child met five of the eight HLH-2004 criteria. A potential viral, bacterial, or fungal trigger was identified in eight children. Eight children were treated with dexamethasone, resulting in the rapid resolution of the hyperinflammatory episode. Conclusion. In the diagnostic work-up of a febrile child with a hematological malignancy, one should always consider an inflammatory condition that may respond favorably to glucocorticoid treatment.
Keywords: adolescent; child; diagnosis, differential; drug therapy; febrile neutropenia; inflammation; lymphohistiocytosis, hemophagocytic; treatment outcome